2013
DOI: 10.1016/j.aim.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Hamilton decompositions of regular expanders: A proof of Kelly’s conjecture for large tournaments

Abstract: A long-standing conjecture of Kelly states that every regular tournament on n vertices can be decomposed into (n − 1)/2 edge-disjoint Hamilton cycles. We prove this conjecture for large n. In fact, we prove a far more general result, based on our recent concept of robust expansion and a new method for decomposing graphs. We show that every sufficiently large regular digraph G on n vertices whose degree is linear in n and which is a robust outexpander has a decomposition into edge-disjoint Hamilton cycles. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
207
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 111 publications
(209 citation statements)
references
References 43 publications
2
207
0
Order By: Relevance
“…A very general result in this direction was obtained very recently by Kühn and Osthus [25], who showed that every regular 'robustly expanding' digraph of linear degree has a decomposition into edge-disjoint Hamilton cycles. The initial motivation for this result was that it implies that every (large) regular tournament has a Hamilton decomposition, which proved a long-standing conjecture of Kelly.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A very general result in this direction was obtained very recently by Kühn and Osthus [25], who showed that every regular 'robustly expanding' digraph of linear degree has a decomposition into edge-disjoint Hamilton cycles. The initial motivation for this result was that it implies that every (large) regular tournament has a Hamilton decomposition, which proved a long-standing conjecture of Kelly.…”
Section: Introductionmentioning
confidence: 96%
“…The initial motivation for this result was that it implies that every (large) regular tournament has a Hamilton decomposition, which proved a long-standing conjecture of Kelly. However, as observed in [26], the main result of [25] has a number of further applications. For instance, it can be used to show an analogue of Conjecture 1 for random tournaments, which confirms a conjecture of Erdős.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To see that the digraphs considered in Theorem 4 are robust outexpanders, we refer the reader to Lemma 11 of [22]. The fact that the graphs in Theorem 2(i) are robust outexpanders is proved in Lemma 12.1 of [21]. Lemma 6.2 of [15] shows that the oriented graphs considered in Theorem 2(ii) are outexpanders.…”
Section: · · · Dmentioning
confidence: 99%
“…Theorem 5 is also used as a tool in a paper by Kühn and Osthus [21], which shows that if a digraph G is a robust outexpander whose minimum semi-degree is linear in n, then G has a Hamilton decomposition. More precisely, the fact that Theorem 5 is algorithmic is used in [21] to provide an algorithm which finds the above Hamilton decomposition in polynomial time.…”
Section: · · · Dmentioning
confidence: 99%